Evaluation of a national e-booking system for medical consultation in primary care in a universal health system. (May 2023) - Motulsky, Aude; Bosson-Rieutort, Delphine; Usher, Susan; David, Geneviève; Moreault, Marie-Pierre; Gagnon, Marie-Pierre; Schuster, Tibor; Sicotte, Claude
Highlights: e-Booking system in primary care practice is appreciated by patients. The national e-booking system had a low adoption across the province. The system was poorly aligned with the diversity of primary care practices. More than 41% of the appointments were not booked online by patients. e-booking system promotes accessibility, but only for a segment of the population. Abstract: Purpose: The Rendez-vous Santé Québec is a national online booking (e-booking) system of medical appointments in primary care rolled out in 2018 in Québec (Canada). The objectives of this study were to describe the adoption by targeted users, and analyze the facilitating and limiting factors at the technological, individual and organizational levels to inform policy makers. Methods: A mixed methods evaluation was conducted involving interviews with key stakeholders ( n = 40), audit logs of the system in 2019, and a population-based survey ( n = 2 003). All data were combined to analyze facilitating and limiting factors, based on the DeLone and McLean framework. Results: The RVSQ e-booking system had a low adoption across the province mainly because it was poorly aligned with the diversity of organizational and professional practices. The other commercial e-booking systems already used by clinics seemed better adapted to interdisciplinary care, patient prioritization and advanced access. e-Booking system was appreciated by patients, but has implications for the performance of primary care organization that goes beyond scheduling management issues, with potential detrimental consequences for care continuity and appropriateness. Further research is needed to define how e-booking systems could support a better alignment between primary care innovative practices and improve the fit between patients' needs and resources availability in primary care.